2023
DOI: 10.1007/s00248-023-02200-2
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the Phototherapeutical Potential of Fungal Pigments in Various Fruiting Body Extracts with Informed Feature-Based Molecular Networking

Abstract: Fungal pigments are characterized by a diverse set of chemical backbones, some of which present photosensitizer-like structures. From the genus Cortinarius, for example, several biologically active photosensitizers have been identified leading to the hypothesis that photoactivity might be a more general phenomenon in the kingdom Fungi. This paper aims at testing the hypothesis. Forty-eight fruiting body-forming species producing pigments from all four major biosynthetic pathways (i.e., shikimate-chorismate, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Can cinnabarin content be manipulated by different wavelengths of light? This is of particular interest as our previous studies already indicated that P. cinnabarinus extracts have promising photochemical activity [ 21 ]. Thus, we wanted to understand the irradiation requirements for the formation of photochemical compounds in pure cultures of this bracket fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Can cinnabarin content be manipulated by different wavelengths of light? This is of particular interest as our previous studies already indicated that P. cinnabarinus extracts have promising photochemical activity [ 21 ]. Thus, we wanted to understand the irradiation requirements for the formation of photochemical compounds in pure cultures of this bracket fungus.…”
Section: Introductionmentioning
confidence: 99%